Childhood Welfare Exposure and Economic Outcomes for Adult Daughters and Sons - Hartley, Robert Paul (2025)
We investigate how length of time on welfare during childhood affects economic outcomes in early adulthood. Using intergenerationally linked mother-child pairs from the Panel Study of Income Dynamics, we adopt a nonlinear difference-in-differences framework using the 1990s welfare reform to estimate average and quantile treatment effects on intensity of welfare use and earnings in adulthood. The causal estimates indicate that additional childhood welfare exposure leads to more adulthood years on the broader safety net for both daughters and sons, yet this positive relationship only applies below moderate levels of adult welfare participation and reverses at greater levels of dependence. Increasing childhood welfare exposure implies lower earnings in adulthood for daughters, however we find no evidence that it depresses adult sons’ earnings. Both daughters and sons exhibit some wage penalty from childhood welfare exposure, yet only daughters are penalized through hours worked in the labor market.